2019
DOI: 10.1002/sdr.1628
|View full text |Cite
|
Sign up to set email alerts
|

System Dynamics Review and publications 1985–2017: analysis, synthesis and contributions

Abstract: System Dynamics Review (SDR) is an important journal for the system dynamics field and its researchers. This article offers a systematic review of the system dynamics articles published in SDR and other related academic journals between 1985 and 2017. The study classifies the material by using a bibliometric analysis of 498 articles in SDR and 943 articles in other journals that are included in the Web of Science database. The results suggest that the most cited authors within SDR have published research in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…Kunc and associates [ 16 ] indicate that there was a significant and increasing trend in SD publications after 2010 in the areas of health improvement, health services, health epidemics, and health policy-making, although the trends were significantly more dramatic than those observed in our results. Torres [ 17 ] presented the number of papers cited in the System Dynamics Review Journal and found that only 37% of the citations were from 2000 to 2009.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kunc and associates [ 16 ] indicate that there was a significant and increasing trend in SD publications after 2010 in the areas of health improvement, health services, health epidemics, and health policy-making, although the trends were significantly more dramatic than those observed in our results. Torres [ 17 ] presented the number of papers cited in the System Dynamics Review Journal and found that only 37% of the citations were from 2000 to 2009.…”
Section: Resultsmentioning
confidence: 99%
“…The average and median numbers of included papers among these reviews were 270 and 182, respectively. More specifically, the maximum number of papers used in the published reviews was 1441 [ 17 ], while the minimum number of papers was six [ 23 ].…”
Section: Evaluation Of Review Papersmentioning
confidence: 99%
“…In this paper, a simulation model of the spread of covid-19 at a hypothetical university is reported, and the model is used to estimate effects of different policy measures on containing the spread. The model focused on the dynamics of the system [ 29 ] as affected by behavioral feedback loops [ 30 ], including human reactions to the growing number of cases and the administration’s decision for early closure. The main contribution of this work is to offer insights into the relative effects of different policies to contain an outbreak in a university setting.…”
Section: Discussionmentioning
confidence: 99%
“…Systems theory is a broad area of research and there are different perspectives on systems within the marketing discipline (Löbler 2016). For instance, system dynamics addresses a broad range of problems by formulating dynamic hypotheses as well as testing computer-based simulation models (Sterman 2000; Torres 2019). This is predominantly a quantitative approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To capture the “mental data bases” (Sterman 2018), a participatory approach to mapping system causality, also known as group model building, is key. Group model building (GMB) is a family of collective decision making methods within system dynamics (Bérard 2010; Ricigliano 2016; Torres 2019). GMB involves system stakeholders in the origination of shared mental models of the problems and consensual unravelling of the underlying causes of these problems to support strategic decision-making (Akkermans and Vennix 1997).…”
Section: Literature Reviewmentioning
confidence: 99%